2016
DOI: 10.1556/030.63.2016.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella infection in healthy pet reptiles: Bacteriological isolation and study of some pathogenic characters

Abstract: The fecal samples from 213 captive reptiles were examined, and 29 (13.61%) Salmonella enterica isolates were detected: 14/62 (22.58%) from chelonians, 14/135 (10.37%) from saurians, and 1/16 (6.25%) from ophidians. The isolates were distributed among 14 different serotypes: Miami, Ebrie, Hermannsweder, Tiergarten, Tornov, Pomona, Poona, Goteborg, Abaetetube, Nyanza, Kumasi, Typhimurium, 50:b:z 6 , 9,12:z 29 :1,5, and a non-motile serotype with antigenic formula 1,4,[5],12:-:-. Salmonella typhimurium and 50:b:z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 38 publications
6
27
2
Order By: Relevance
“…The highest level of resistance in this study was observed for streptomycin (7.7%). Resistance to this antibiotic in Salmonella strains derived from reptiles was noted by a number of other authors (Seepersadsingh and Adesiyun 2003;Chen et al 2010;Barazorda Romero et al 2015;Bertelloni et al 2016). A low prevalence of tetracycline resistance was detected in this study (2.6%), which is in agreement with published results (Ebani et al 2005;Sylvester et al 2014).…”
Section: Eublepharis Maculariussupporting
confidence: 93%
See 2 more Smart Citations
“…The highest level of resistance in this study was observed for streptomycin (7.7%). Resistance to this antibiotic in Salmonella strains derived from reptiles was noted by a number of other authors (Seepersadsingh and Adesiyun 2003;Chen et al 2010;Barazorda Romero et al 2015;Bertelloni et al 2016). A low prevalence of tetracycline resistance was detected in this study (2.6%), which is in agreement with published results (Ebani et al 2005;Sylvester et al 2014).…”
Section: Eublepharis Maculariussupporting
confidence: 93%
“…of about 19% in the studied reptiles. Available literature sources have reported varying levels of prevalence, namely, 54.1% in Germany and Austria (Geue and Loschner 2002), 32.6% in Poland (Piasecki et al 2014), 49% in Sweden (Wikstrom et al 2014), 13% in Croatia (Lukac et al 2015), 30.9% in Taiwan (Chen et al 2010) and 13.6% in Italy (Bertelloni et al 2016). Our results did not differ significantly from those obtained in other countries.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Almost half of our isolates (44.6%) showed resistance to tetracycline. Resistance to this antimicrobial has been frequently found in pathogens and commensal bacteria from domestic [16,[63][64][65][66] and wild [58,60,67] animals. Even if β-lactams and tetracycline belong to different antibiotic classes, there could be some shared considerations.…”
Section: Discussionmentioning
confidence: 99%
“…has also been isolated from Russian tortoises and spur-thighed tortoises [2223]. Another recent study recorded antibiotic-resistant S. enterica isolated from chelonians which were also harboring some virulence genes in their plasmids [24]. Besides, S. enterica could be isolated from several popular species of pet turtles and their environment indicating a potential risk of infection to turtle keepers [25].…”
mentioning
confidence: 99%